STRATEGI PENGEMBANGAN POTENSI WISATA RELIGIUS BUKIT KASIH TOAR LUMIMUUT KANONANG KABUPATEN MINAHASA - WALANGITAN, OLIVIA CHRISTINE (Sam Ratulangi University, 2015)
Abstract: a reliable regional tourism industry should have a marketing concept in the form ofmanagement applied to seize the tourism market. The purpose of this study was to determine how thestrategy of development of religious tourism potential Hill Love Toar Lumimuut Kanonang